Patterns of Islamic Education Learning in Applying 2013 Curriculum in SMPN 27 Medan - Ali Imran Sinaga; Salamuddin Salamuddin; Dewi Khairini (BIRCU, 2020)
The research objectives were to find out: (1) how teachers implement Islamic religious education learning in the 2013 curriculum, (2) steps in applying the 2013 curriculum, and (3) problems related to the pattern of Islamic religious education in implementing the 2013 curriculum. The research method used is qualitative research, data collection is carried out in natural conditions and using data collection methods, namely: interview method, observation method, documentation method. Activities in data analysis are: data reduction, data presentation, and drawing conclusions. The research findings show: (1) the teacher first makes a Learning Implementation Plan by paying attention to the aspects of the life skills developed, the media used and the assessments carried out, (2) the learning process is carried out by applying a scientific approach, as well as active learning strategies, including modeling the way, reading aloud, reading guide, group resume, and (3) evaluations conducted by the teacher using an authentic assessment system which includes cognitive aspects, skills aspects, and affective aspects (spiritual and social).